INSTALLING MODEM ROUTER ASYMETRIC DATA SUBSCRINE LINE WITH BROADBAND TECHNOLOGY SYSTEM - Rina Rina; Fivtatianti H, Skom, MM (Jurnal Sistem Komputer, 2008)
On Writing "Installing Modem Router Asymetric Subscrine Data Line (ADSL) WithBroadband Technology System" is used to improve the ability to channel high-speedservice type, to avoid interference between the direction of transmission additions(Upstream) and Download (Downstream).